Effect of Partial Replacement of Cement with Coconut Shell Ash on Concrete Performance - Santosa , Bing; Ginting, Arusmalem; Adi , Prasetya; Manasye , Eliada Obed (Jurnal Teknik Sipil, 2023)
Green concrete is environmentally friendly concrete made using waste or residual materials. Green concrete is made using alternative materials to partially replace cement or aggregate. Coconut shell is a solid waste from coconut processing that has not been utilized optimally so that coconut shell ash needs to be tried to replace some of the cement. The cement substitution with coconut shell ash used was 2.5%, 5.0%, 7.5%, 10%, 12.5%, 15%, 17.5%, 20%, and 22.5% by weight of cement. There are 3 concrete cylinder specimens for each variation and a total of 30 specimens. The tests carried out were slump testing for fresh concrete and compressive strength testing for hard concrete after 28 days. From the research results obtained: coconut shell ash has a high silica content so that it can be used as a pozzolan. Increasing the percentage of cement substitution with coconut shell ash decreases the slump value. The substitution of cement with coconut shell ash increases the compressive strength of concrete. Increasing the percentage of cement substitution with coconut shell ash reduces the compressive strength of concrete. The substitution of cement with coconut shell ash had no significant effect on the volume weight of the concrete.